Monitoring air pollution effects on children for supporting public health policies (MAPEC_LIFE study). (13th November 2019) - Ceretti, E; Donato, F; Feretti, D; Carducci, A; Moretti, M; Donno, A De; Carraro, E; Biggeri, A; Gelatti, U
Abstract: Background: Children are at high risk of suffering health consequences of air pollution and childhood exposure can increase the risk of developing chronic diseases in adulthood. The MAPEC_LIFE project, funded by EU Life+ Programme (LIFE12 ENV/IT/000614), aimed to evaluate the association between air pollution exposure and biomarkers of early effect in children and to propose guidance for implementing environmental policies. Methods: The study was carried out on 6-8-year-old children. Micronucleus (MN) frequency was investigated in buccal cells of children and its association with air pollution exposure was assessed applying multiple Poisson regression mixed models, including socio-demographic and lifestyle factors as confounders. We also dichotomize air pollutants concentration according to the EU Ambient Air Quality Directives and WHO Air Quality Guidelines in all Poisson regression models to assess their risk predictive capacity. Results: The project involved 1149 children providing buccal cells in winter and spring. 2139 biological samples were included in the analysis (1093 collected in winter, 1046 in spring). The analysis of the association between MN frequency and air quality parameters found positive associations for PM10, PM2.5, benzene, SO2 and ozone. Considering EU Directives, an association was found between MN frequency and PM10 exposure higher than the annual limit value, with an increase of the risk of 17.9% (95%CIs: 0.6-38.1%). Considering WHO Guidelines, the exposures to levels of PM10, benzene and BaP higher than the annual limits were associated with MN frequency, with a risk increase of 22.5%, 27.8% and 59.8% (95%CIs: 3.9-44.3%, 3.8-57.3%, 21.0-111.1%), respectively. Conclusions: The analyses conducted showed an association between MN frequency in buccal cells of children and levels of some air pollutants, even at concentration below EU and WHO thresholds, which hence seemed to be insufficient for protecting children from this type of damage. Key messages: Air pollution exposure induced chromosomal damage in buccal cells of children, even at concentration below the law limits. Early biological damage detected might be predictive of the occurrence of future harmful effects in humans, at a population level.